Assessing the Impact of Proximate and Non-Proximate Determinants of Fertility in Namibia: A Structural Equation Modelling Approach (Namibian Journal for Research, Science and Technology, 2022)
Fertility rate has been declining over the years in Namibia, and a number of studies have been conducted to investigate how socio-economic and physiological factors influenced fertility decline. This study was aimed at modelling the direct and indirect effects of socio-economic, socio-demographic and health attributes on fertility, as well as the proximate and  nonproximatedeterminants of fertility using the Structural Equation Modelling (SEM) technique and the data from the 2013 Namibia Demographic Health Survey. To be precise, the confirmatory factor analysis part of the SEM technique was used to test the theorized model of the proximate and non-proximate determinants of fertility, while the factor modelling part was used to measure the effects that these two constructs of fertility determinants had on fertility. Results from this study showed that the proximate determinants had a direct negative impact β = -0.023) on the number of children ever born, while there was a (significant) positive effect β = 0.053) between the non-proximate determinants and the number of children ever born. In addition, age at first birth had a (significant) positive effect on the number of children ever born by Namibian women while the effect of contraceptive use was found to have a minor effect. Moreover, women who had their first birth at the beginning of their reproductive period were more likely to have more children born to them, while women who had their first marriage at younger ages were more likely to have more children. It is therefore recommended that there is a need to promote contraceptive use among Namibian women to further reduce fertility, especially among women from poor households as the cost of rising children has become high as the year progresses. Additionally, there is also a need to promote and strengthen the education of young females in order to increase their age at first birth and at first marriage in Namibia.
Keywords: Fertility; Namibia; Structural Equation Model